The mediating effects of training motivation on assignment methods and transfer of training: the Malaysian context - Mohd Zainol, Noor Azmi; Abdul Ghani, Ahmad Bashawir; Ismail, Azman; Yaacob, Safar; Subhan, Muhammad; Joarder, Mohd Hasanur Raihan (Medwell Journals, 2016)
The objective of this study is to examine the mediating effects of training motivation in the relationship between assignment methods and transfer of training using data gathered from survey questionnaires on military intermediate level officers in Malaysia. The statistical tool SmartPLS was employed to test the research hypotheses. The result indicated that training motivation was found to be an important mediator in the hypothesized relationship in Malaysian context. The study is significant particularly for training administration department and organizational managers directly related to training. Further, this study provides discussion, implications and conclusion.